COMPARATIVE BIOEQUIVALENCE STUDIES OF CINNARIZINE AND ITS DIFFERENT AVAILABLE MARKETED FORMULATION DRUGS - KUMAR, SANJEEV; M, AMIN MIR; KUMAR, SARVESH; KUMAR, ANUJ (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The main focus of the study was to investigate the marketed formulations of cinnarizine and it is marketed analogous. Methods: The study involved the analysis of basic pre-formulation studies, namely, physical properties, melting point, Fourier-transform infrared, loss on drying, assay of cinnarizine, standard curve, and partition co-efficient of various marketed tablets of cinnarizine. Results: Cinnarizine is an H1-receptor antagonist drug which is widely used for the treatment of dynamical sickness, vomiting, and vertigo. In this study, five known marketed formulations of cinnarizine were evaluated for weight variation, hardness, drug content, friability, disintegration time, and in vitro dissolution as well as the drug release kinetics of the tablets. As per the study, the drugs show low disintegration time and good hardness, also in vitro dissolution studies have shown near about 90% drug release at the end of the first 10 min and then cumulative drug release of not less than 92% in the nearby 10 min. Hence, these formulations show lower friability, acceptable taste, and shorter disintegration time which make them suitable to be accepted. Thus, the tablets are good for the use, so allow them to be marketed for the wellbeing of humans. Conclusion: It had been found that all the tablets show acceptable limits for various parameters of analysis, in a sustained manner. Thus, all the tablets are effective for usage under standard conditions.